DIETARY ADENINE ALLEVIATES FATTY LIVER INDUCED BY OROTIC ACID - Yohanes Buang (Indonesian Journal of Chemistry, 2010)
The effects of dietary adenine in fatty liver induced by orotic acid (OA) were studied. Rats were paired-fed 1% OA-supplemented diets with/or without 0.25% adenine or a diet without OA for 10 days. Serum lipid profiles were measured using enzyme assay kits. Lipids of liver tissues were extracted and liver lipid contents were determined. A peach of liver was prepared to determine the activities of fatty acid synthase (FAS) and fatty acid β-oxidation. The results showed that liver TG content of OA-fed rats increased markedly in comparison to basal group.  However, the addition of adenine to the diet reversed promotion of liver TG content to basal level. It was also found that FAS activities decreased. Furthermore, these diets reversed the inhibition of fatty acid β-oxidation to basal level and induced the serum lipid levels secretion. Therefore, the alleviation of fatty liver in OA-treated rats given dietary adenine is associated with the inhibition of FAS activities accompanied with the promotion of mitochondrial fatty acid β-oxidation and the promotion of serum lipid secretion from the hepatic tissue into the bloodstream.